Cinema 4D Essential Training: 3 Cameras Animation and Deformers. - Garrott, Rob (linkedin.com, 2012)
Focuses on the basics of animating in CINEMA 4D, including setting keyframes, moving the camera, and adding movement and interest with deformers.